Biographical approach in pedagogical research: from life story to monograph - Medveckis, Arturs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Pedagogical researches on educational system or the history of some educational establishment traditionally deal with documents reflecting the institution establishment regulatory documents, structure, management hierarchy, education content and regulatory upbringing documents. For deeper focus on pedagogical research biographical approach is useful. This article looks at three publications of different genres written and compiled by the author of this publication. These are Liepāja University Academic Staff Biographical Index, Liepāja University Staff Life Stories published in three books and a monograph about the Liepāja University women’s choir “Atbalss” conductor and music teacher Kārlis Rūdolfs Kreicbergs. Creation of the editions is based on extensive empirical data biographical research. The article highlights specificity of three newly-created works. Basing on methodology of creating these works and their further analysis a system-oriented view on pedagogical paradigm of the period, characterising the collisions between personalities and the period, was developed